Time Materialized – Broaching the Question of Objective Historicity - Nielsen, Thor Hennelund (Res Cogitans, 2020)
The paper unfolds a preliminary theory of so-called objective or ontological historicity, that is to say, a theory of historicity which is not founded in the human subject. The article does this by deriving a notion of historicity from classical ontology by drawing upon figures such as Aristotle, Cusanus, Leibniz and Kant. One of the leading examples analysed throughout the paper is the museal object, which seems to embody a certain aporia between an immediate presence and the presence of a bygone era and time. It is argued that the historical objects qua historical objects exhibit a certain monadic quality, but that the relation between the different aspects of the object remain an irreconcilable one.